2010
DOI: 10.29309/tpmj/2010.17.02.2371
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of Pancytopenia

Abstract: Background: Pancytopenia is a reduction in the number of each type of peripheral blood cell. Therefore the role of bone marrow examintion in diagnosis of pancytopenia is important to know etiology of pancytopenia. The objective of the study was to know the aetiology of pancytopenia. Methods: This descriptive (Cross sectional) study was carried out in Khyber teaching hospital. Fifty patients with pancytopenia were included in the study from 1st January 2008 to 30th October 2008. Full blood counts, bone marrow e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 1 publication
1
6
2
Order By: Relevance
“…We reported hepatomegaly in 12.6% of cases. Rehmani et al and Tariq et al reported similar findings in their studies [ 14 , 17 ]. However, a higher prevalence of hepatomegaly was reported in a few other studies [ 5 , 6 , 15 , 18 ].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…We reported hepatomegaly in 12.6% of cases. Rehmani et al and Tariq et al reported similar findings in their studies [ 14 , 17 ]. However, a higher prevalence of hepatomegaly was reported in a few other studies [ 5 , 6 , 15 , 18 ].…”
Section: Discussionsupporting
confidence: 75%
“…Splenomegaly was the second most common clinical finding found in our study observed in 22% of cases. Jain et al [ 20 ] and other studies [ 14 , 17 ] reported splenomegaly in similar frequency, while Khunger et al and Khodke et al observed splenomegaly in 32.5% and 40% of patients, respectively [ 5 , 15 ]. We reported hepatomegaly in 12.6% of cases.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Pancytopenia is a clinical condition characterized by decrease in count of all cell lines in peripheral blood that is anemia (hemoglobin less than 12-14 gm/dl taking in account age and sex of patient), leucopenia (white cell count less than 4500×109/L) and thrombocytopenia( total platelet count less than 150000×109/L) [4]. Depending on the degree of each cytopenia, pancytopenia is further catalogued into mild moderate or severe.…”
Section: Discussionmentioning
confidence: 99%